Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.1111/j.1471-8286.2005.00891.x
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of polymorphic microsatellites in Parnassius apollo and Euphydryas aurinia (Lepidoptera)

Abstract: Microsatellite loci were developed from Parnassius apollo and Euphydryas aurinia, two endangered Palaearctic butterfly species. Respectively, six and five polymorphic loci were characterized from an enriched partial genomic library. Genetic diversity range from three to 25 alleles for the first species and from seven to 21 for the second. Although the presence of null alleles is suspected, these polymorphic loci are likely to provide important information on the fine scale genetic structure among populations o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 10 publications
(13 reference statements)
2
14
0
Order By: Relevance
“…In particular, in other Parnassius sp. populations studied with microsatellite loci (MeglŽcz et al 1998;Keyghobadi et al 1999Keyghobadi et al , 2002Petenian et al 2005), the observed heterozygosity ranges between 0.33Ð0.68, a range into which our results fit well.…”
Section: Differences In Genetic Diversitysupporting
confidence: 75%
“…In particular, in other Parnassius sp. populations studied with microsatellite loci (MeglŽcz et al 1998;Keyghobadi et al 1999Keyghobadi et al , 2002Petenian et al 2005), the observed heterozygosity ranges between 0.33Ð0.68, a range into which our results fit well.…”
Section: Differences In Genetic Diversitysupporting
confidence: 75%
“…This study also confirmed the successful use of two established microsatellite loci for the study species, although they both showed considerable deviations from HWE across the sampled populations [16]. Such deviations in HWE, aside from being the result of null alleles, can be expected in E. aurinia and other Lepidoptera with similar life histories, for several biologically plausible reasons.…”
Section: Discussionsupporting
confidence: 78%
“…A differently labelled M13 primer can be used for each multiplex and then all multiplexes can be combined when sequencing. We also synthesized previously published primers of E. aurinia microsatellite markers [16], [34] with the addition of a M13 tail and tested these on our samples.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our studies showed that the PIC of S. inferens SSRs ranged from 0.181 to 0.947; the mean was 0.633, which indicates a relatively high polymorphism. It has been difÞcult to isolate microsatellite markers for Lepidoptera species (Anthony et al 2001, Petenian et al 2005, Fauvelot et al 2006, VanÕt Hof et al 2007, Habel et al 2008, Sinama et al 2011 possibly because loci contain similar ßanking regions (Meglecz et al 2004(Meglecz et al , 2007, are associated with transposable elements (Coates et al 2008, Tay et al 2010, or contain a high frequency of null alleles (Keyghobadi et al 1999, Harper et al 2003, Meglé cz et al 2004, Zhang, 2004, VanÕt Hof et al 2007, Mikheyev et al 2010. Our result showed that 12 loci (boldface in Table 1) exhibited no signiÞcant evidence of null alleles in ampliÞed loci with high polymorphism (PIC Ͼ 0.5), which accounted for merely half of the highly polymorphic loci (PIC Ͼ 0.5; Table 1).…”
Section: Resultsmentioning
confidence: 99%